Spontaneous Transvaginal Sigmoid Colon Evisceration and Sepsis from Complete Procidentia - Schefter, Alexandra M. (Female Pelvic Med Reconstr Surg, 2018)
BACKGROUND: Transvaginal bowel evisceration is an exceptionally rare event. Most reported cases are of small bowel evisceration in postmenopausal woman who have undergone hysterectomy. CASE: Here, we report an isolated case of complete procidentia and spontaneous sigmoid colon evisceration leading to sepsis in an 89-year-old woman with no surgical history. CONCLUSION: We highlight the risk factors, clinical presentation and treatment options for this unique multidisciplinary emergency.